PENGARUH PENGGAJIAN DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT.SAMUDERA AGENCIES INDONESIA CABANG BATAM - manik, pinta; fullah, Syai (SCIENTIA JOURNAL, 2021)
This research aims to determine the impact of wages and rewards on employee performance at PT. Samudera Agencies Indonesia Cabang Batam at the same time or in part. This study uses a descriptive study using quantitative methods. Collect data by distributing questionnaires to 100 respondents. Data analysis techniques used validity test, reliability test, normality test, multiple clonality test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis, T test and F test, using SPSS version program 25. The results of this research show that wages (X1) and incentives (X2) have a positive and significant impact on employee performance (Y). According to the calculated F test result, it is found that df1=k1 then 31=2, df2=nk or 1003=97, then the result obtained from Table F is 3.09. According to the results in the above table, the calculated F value is known to be 25.295. Because the calculated F value is greater than Table F and the significance value is 0.000<0.05, it can be concluded that wages and incentives affect employee performance.